ESTRUTURA DA COMUNIDADE E ECOMORFOLOGIA DOS PEIXES DA BAÍA DE TURIAÇU, MARANHÃO-BRASIL. - LINO, Meriane de Jesus Costa (2014)
Understanding how fish use the resources found in the region of Turiaçu Bay, as well as its ecological relationships in this environment, are important for decision-making in the management and conservation of this ecosystem. Therefore, the The objective of this study is to analyze the fish community of Turiaçu Bay, characterizing the structural and morphological patterns of the community related to the use of resources by fish. A total of 1,176 individuals were identified belonging to 62 species, distributed in 8 orders and 21 families, classified in trophic and ecological guilds. Morphological patterns of the most abundant families: Sciaenidae, Ariidae and Engraullidae, related to the trophic behavior. Thus, it was observed that there is a predominance of species generalists with a strong tendency to carnivore and who seek the estuary to complete some stage of its life cycle. In addition, patterns were found ecomorphological differences, which were reflected in the morphological differences found among the trophic categories. Thus, it is concluded that the fish community of Turiaçu Bay, is well diversified, sheltering a variety of species including of commercial value, and who use this environment for food and shelter in accordance with with their different morphological adaptations.